Perangkat Lunak Restoran Dan Rumah Makan Halal Di Kota Palembang Berbasis Android - Lambardo, Fakhri; Zamin, Muhammad (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Information about halal restaurants and restaurants is needed by the community in Palembang City. This is because there are still many restaurants and restaurants that have not put halal labels on their place of business. Therefore, people need an application that makes it easier for people to find out information about halal restaurants and restaurants. Community problems are inseparable from the cellphone that people must call if they want to take a break in restaurants and restaurants labeled halal This relates to the use of appropriate and varied applications in the process of halal restaurants and restaurants can find out halal restaurants and restaurants in android and can reduce the attitude of users who have to use phones